AB209630, a long non-coding RNA decreased expression in hypopharyngeal squamous cell carcinoma, influences proliferation, invasion, metastasis, and survival - Zhou, Jieyu (Oncotarget, 2016)
Long noncoding RNAs (lncRNAs) are associated with the development, progression, and prognosis of human cancers. However, the clinical significance and biological function of lncRNAs in hypopharyngeal squamous cell carcinoma (HSCC) remain largely unknown. We characterized the novel lncRNA AB209630 in vivo and in vitro. First, using qRT-PCR, we evaluated whether AB209630 levels differ between HSCC tissues/cell lines and adjacent normal tissues/cell lines. We then assessed whether AB209630 expression levels stimulate or inhibit proliferation, invasion, apoptosis, and metastasis in vitro. Finally, we investigated whether AB209630 levels in tumor tissues were associated with survival outcomes. Our results demonstrated that AB209630 levels were markedly lower in HSCC tissues and cells than in normal tissues and cells, and increased expression of AB209630 level significantly inhibited growth, metastasis, and invasion and stimulated apoptosis in vitro. In addition, patients with decreased expression of AB209630 had a significantly poorer prognosis than those with high AB209630 expression. These data suggest that increased expression of AB209630 might either stimulate or inhibit biological activities involved in HSCC development, indicating a potential application of AB209630 in future treatment for this disease. This study suggest that AB209630 functions as a tumor suppressor in HSCC, and its decreased expression may help predict a poor prognostic outcome of HSCC. Our future work will focus on the mechanisms of whether and how AB209630 as a tumor suppressor gene is involved in HSCC development.